PENGARUH ORIENTASI ETIKA DAN KOMITMEN PROFESIONAL TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI MELALUI RASIONALISASI SEBAGAI VARIABEL MODERATING - Imang Dapit Pamungkas (Fakultas Ekonomi Universitas Pekalongan, 2017)
This study aimed to examine the effect of ethical orientation of idealism and relativism against Fraud Trends in Accounting, Professional Commitment to Accounting Fraud Trends and Impact Orientation Ethics and Professional Commitment Accounting Fraud against the trend through Rationalization asModerating Variable. Sampling is purposive sample selection method used in this study. The sample in this study were 129 students S1 Accounting Pekalongan University who has taken the course of AuditI. Hypothesis testing using multiple regression by using SPSS version 20. Results of hypothesis testing showed that idealism affect the tendency of Accounting Fraud accepted. Relativism against Accounting Cheating tendency rejected. Professional Commitment affect the tendency of Accounting Fraud accepted. Idealism and commitment to the tendency of Professional Accounting Fraud through Rationalization as Moderating Variable accepted. However, the tendency towards relativism Accounting Fraud through Rationalization as Moderating Variable rejected.Keywords: Ethics Orientation, Professional Commitment, Accounting Fraud Trends, Rationalization